Two new Aphnaeus (Lepidoptera: Lycaenidae: Theclinae) species from Liberia - Sáfián, Szabolcs; Libert, Michel; Collins, Steve C. (Zootaxa, 2013)
Two new butterfly species belonging to the genus Aphnaeus (Lycaenidae: Theclinae), A. mirabilis sp. n., A. nimbaensis sp. n. were found in the Nimba Mountains, Western Range, Liberia in February 2012. Both are illustrated and described in comparison with closely related species: A. flavescens Stempffer, 1954 and A. liberti Bouyer, 1996, respectively. Genitalia of the male holotype of A. nimbaensis are also illustrated.